2021
DOI: 10.1002/jmv.27037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of T lymphocytes in severe COVID‐19 patients

Abstract: In this observational study, 13 patients with severe COVID‐19 and 10 healthy controls were enrolled. The data concerning the analysis of circulating T cells show that, in severe COVID‐19 patients, the expansion of these cell compartments is prone to induce antibody response, inflammation (CCR4+ and CCR6+ TFH) and regulation (CD8+ Treg). This pathogenic mechanism could lead us to envision a possible new form of biological target therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
4
19
2
1
Order By: Relevance
“…The frequencies of PD-1 + ICOS + cTfh, cytotoxic CD4 + T and exhausted T cells were strongly expanded in COVID-19 patients, particularly in severe patients compared to healthy individuals, which suggested that extensive T cell dysfunction was associated with COVID-19 severity (162). In severe COVID-19 patients, the frequencies of CCR6 + cTfh cells and CCR4 + cTfh cells were expanded, but CCR3 + cTfh cells and Th1 cells were low in severe COVID-19 patients compared to healthy individuals (163). The frequencies of PD-1 + ICOS + cTfh cells, activated cTfh cells and cytotoxic CD8 + T cells were strongly upregulated in COVID-19 patients, particularly in severe patients compared to healthy donors.…”
Section: Tfh Cells In Sars-cov-2 Infection and Vaccinementioning
confidence: 94%
“…The frequencies of PD-1 + ICOS + cTfh, cytotoxic CD4 + T and exhausted T cells were strongly expanded in COVID-19 patients, particularly in severe patients compared to healthy individuals, which suggested that extensive T cell dysfunction was associated with COVID-19 severity (162). In severe COVID-19 patients, the frequencies of CCR6 + cTfh cells and CCR4 + cTfh cells were expanded, but CCR3 + cTfh cells and Th1 cells were low in severe COVID-19 patients compared to healthy individuals (163). The frequencies of PD-1 + ICOS + cTfh cells, activated cTfh cells and cytotoxic CD8 + T cells were strongly upregulated in COVID-19 patients, particularly in severe patients compared to healthy donors.…”
Section: Tfh Cells In Sars-cov-2 Infection and Vaccinementioning
confidence: 94%
“…The low levels of somatic hypermutation among responding B cells following severe infection is consistent with an impaired GC response and may lead to the production of antibodies that are unable to mediate disease resolution. However, a robust circulating T FH cell response is detectable in the blood of many severely infected individuals, suggesting that the GC response is not defective in all cases 54 56 . Impaired disease resolution in severely infected individuals may also be caused in part by impaired T cell-mediated clearance of virally infected cells 19 , 52 , 57 60 .…”
Section: B Cell Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…On the contrary, no significant alterations were described in peripheral blood [ 115 , 116 , 48 , 49 ] for T follicular helper cells (Tfh). Data on T regulatory cells are highly heterogeneous, with some reports showing an increase while some others showing a decrease in the circulation of severe COVID-19 patients [ 117 , 118 ]. Lymphopenia occurring in severe COVID-19 affects also the B cell compartment.…”
Section: Lymphopeniamentioning
confidence: 99%